Theoretical and methodological approaches to development of the "road map" for promoting a new medicine product to the pharmaceutical market - Olkhovska, Anzhela; Malyi, Volodymyr (Національний фармацевтичний університет, 2019)
The aim of the article is to develop theoretical and methodological approaches to composing the “road map” to promote a new medicine product (МР) to the market. The methodological basis of the research is the statements of the Ministry of Health of Ukraine, analytical companies of the pharmaceutical market, scientific publications and reports. During the research we used the following methods, namely: marketing, system-based and analytical, modeling, logical analysis and generalization, structural grouping, “road mapping”. Results and discussion. The article indicates that “road maps” are one of the most effective tools for solving problems to enhance innovative potential and for improving the process of making strategic decisions to promote a new MP to the market, which are successfully applied by a number of foreign high-tech companies. We have developed the model of the “road map” for promoting a new MP to the pharmaceutical market, as well as detailed implementation of its stages. Conclusions. The model of the “road map” was developed to promote a new MP to the market, the implementation of which will ensure pharmaceutical enterprises to effectively market the product, by taking strategic decisions on defining the communicative and economic efficiency of the promotion process. We have proposed the methods of risk modeling while implementing the “road map” model for promoting MP to the market.

Метою роботи є розробка теоретичних та методичних підходів до складання «дорожньої карти» просування нового лікарського засобу (ЛЗ) на ринок. Методологічну основу дослідження склали звіти МОЗ України, аналітичних компаній фармацевтичного ринку, наукові публікації та доповіді. У процесі дослідження використовувалися такі методи: маркетингові, системно-аналітичні, моделювання, логічного аналізу та узагальнення, структурного групування, дорожнього картування. Результати та їх обговорення. У статті зазначено, що одним з найбільш ефективних інструментів вирішення завдань з активізації інноваційного потенціалу та вдосконалення процесу прийняття стратегічних рішень з просування на ринок нового ЛЗ є «дорожні карти» (road maps), які успішно застосовуються рядом зарубіжних високотехнологічних компаній. Розроблено модель «дорожньої карти» просування нового лікарського засобу на фармацевтичний ринок та деталізована практична реалізація її етапів. Висновки. Розроблено модель «дорожньої карти» просування нового лікарського засобу на ринок, практична реалізація якої дозволить фармацевтичним підприємствам ефективно просувати товар на ринок, поетапно приймаючи стратегічні рішення з визначенням комунікативної та економічної ефективності процесу просування. Запропоновані методи моделювання ризику при практичній реалізації моделі «дорожньої карти» просування лікарських засобів на ринок.
Keywords: medicine product; pharmaceutical market; "road map"; model; promotion; marketing communications; лікарський засіб; фармацевтичний ринок; "дорожня карта"; модель; просування; маркетингові комунікації